Securitization Of Clandestine Drug Laboratories: The Role Of Interpol's National Central Bureau (Ncb) In Indonesia In Arresting Roman Nazarenko - Zsa Zsa Haura Khairunnisa Br G (POLTRANS: Journal of Politics and Social Transformation, 2025)
This study examines the securitisation process implemented by Indonesia’s Interpol National Central Bureau (NCB) in the arrest of Roman Nazarenko, a fugitive identified as the mastermind behind clandestine drug laboratories. Distinct from previous studies that positioned narcotics as the primary existential threat, this research demonstrates that an individual, Nazarenko, can represent the core threat due to his transnational capacity to establish illicit drug manufacturing. Employing a qualitative approach with purposive sampling, data were collected through an in-depth interview with a key NCB official. They were analysed using the Miles and Huberman model (comprising data reduction, data display, and conclusion drawing). Applying Copenhagen School securitisation theory, the study finds that the NCB framed Nazarenko as a critical security threat by issuing an Interpol Red Notice, which functions as a concrete speech act. The effectiveness of this process is reflected in NCB Interpol Thailand’s rapid arrest of Nazarenko at U-Tapao Rayong Airport, which evidences not only threat construction but also real-world audience acceptance and coordinated law enforcement action. By shifting the referent object of securitisation from substance to individual, this study elucidates how NCB Interpol Indonesia dynamically constructs, legitimises, and internationalises new security threats. The findings provide fresh insights into operational mechanisms and underscore the crucial role of international collaboration in combating transnational organised crime.